Low-cost high-efficiency transfer printing coating and preparation method thereof
By using a transfer coating composed of modified functional starch and nanocellulose hydrogel on the surface of the thermal sublimation transfer paper, the fluidity barriers caused by high viscosity and low viscosity and the penetration problems under ink are solved, and the low-cost and high-efficiency transfer effect is achieved, and the strength and durability of the paper are improved.
Patent Information
- Application Number
- CN202510207693.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-25
AI Technical Summary
The existing thermal sublimation transfer paper surface coatings have problems such as high viscosity leading to fluidity barriers and low viscosity leading to ink penetration, and are costly and difficult to meet the wet strength requirements of large high-speed coating machines.
The low-cost and high-efficiency transfer coating consisting of modified functional starch, nanocellulose hydrogel, kaolin and water is used to improve the viscosity, solid content and drying performance of the coating through the cationization treatment of modified functional starch and the introduction of nanocellulose.
The coating is achieved with low viscosity, high solids content and good drying performance, and the wet strength requirements of low-quantitative paper running on large and high-speed coating machines are met, which reduces costs, and improves the transfer effect and paper strength and durability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of printing coatings, and in particular to a low-cost and high-efficiency transfer coating and a preparation method thereof. Background Art
[0002] Thermal sublimation transfer technology is an emerging printing process. It pre-prints the pattern on the transfer paper surface, and then transfers the exquisite pattern on the transfer paper to the product surface through a thermal transfer machine by heating and pressurizing at one time. After forming, the ink layer is integrated with the product surface, which is realistic and beautiful, with good reproducibility, and can meet the requirements of the designer, greatly improve the grade of the product, and is suitable for mass production. At the same time, it is also particularly suitable for producing a small number of diverse personalized and customized products, as well as printing patterns containing full-color images or photos.
[0003] As the core medium of this technology, the performance of thermal sublimation transfer paper is directly related to the transfer effect. At present, optimizing the coating formula of paper surface to improve transfer efficiency is the future development trend of this field.
[0004] The most important component of thermal sublimation transfer paper is its surface coating. Existing coating formulation systems generally have low solid content, high viscosity, and poor drying performance, which makes it difficult to meet the wet strength requirements of low-weight paper running on large, high-speed coating machines. And with the trend of lightweight paper, the functional requirements for transfer coatings are becoming more and more stringent. The sublimated ink will diffuse outward from the back of the paper page, affecting the transfer effect. Therefore, it is necessary to overcome the fluidity barriers caused by the high viscosity of the coating and the problem of low-viscosity ink penetration, and also take into account the adaptability of ultra-low-weight paper. In addition, as a process paper, thermal transfer paper is used in huge quantities. The higher the cost, the greater the waste. Reducing costs is also the goal pursued by this technology.
[0005] Therefore, it is necessary to develop a thermal transfer coating with low cost, high transfer rate and suitable for rapid transfer on ultra-low quantitative transfer paper. Summary of the invention
[0006] The purpose of the present invention is to provide a low-cost and high-efficiency transfer coating and a preparation method thereof, which are used to solve the technical problems that the high viscosity of the surface coating of thermal sublimation transfer paper easily leads to fluidity obstruction and the low viscosity leads to ink penetration.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a low-cost and high-efficiency transfer coating, which is composed of the following components in parts by mass: 5-40 parts of modified functional starch; Nanocellulose hydrogel 2-10 parts; Kaolin 0-40 parts; 10~100 parts of water; The preparation method of the modified functional starch comprises the following steps: The starch and the alkali metal hydroxide are mixed and subjected to an esterification reaction to obtain esterified starch; adding anhydride solution to esterified starch to react and obtain sulfonated precursor starch; The sulfonating agent is added to the sulfonated precursor starch to carry out a sulfonation reaction, and the product is washed, dried and crushed in sequence to obtain the modified functional starch.
[0008] Further, the molar ratio of the starch to the alkali metal hydroxide is 10:1-5, and the alkali metal hydroxide comprises sodium hydroxide; The temperature of the esterification reaction is 30-80° C., and the time of the esterification reaction is 20-60 min.
[0009] Furthermore, the starch comprises one or more of wheat starch, corn starch, potato starch and bean starch; When the acid anhydride solution is added to the esterified starch for reaction, the reaction temperature is 30-80° C. and the reaction time is 2-7 hours; The molar ratio of the acid anhydride to the esterified starch in the acid anhydride solution is 1:1-1.5.
[0010] Furthermore, the molar ratio of the sulfonating agent to starch is 0.5-1.5:3, the temperature of the sulfonation reaction is 30-80° C., and the time of the sulfonation reaction is 2-4 hours; The sulfonating agent comprises one or more of fuming sulfuric acid, chlorosulfonic acid, sulfur trioxide, aminosulfonic acid and sulfite.
[0011] Furthermore, the preparation method of the nanocellulose hydrogel comprises the following steps: The plant fibers are sequentially subjected to irradiation degradation, mechanochemical modification, and high-pressure homogenization treatment to obtain nanocellulose hydrogel; The nanocellulose hydrogel has a solid content of 1-5%, a diameter of 3-5 nm, and a length of 500-1000 nm.
[0012] Furthermore, the plant fiber comprises one or more of natural wood pulp, bamboo pulp or cotton pulp; The radiation degradation dose of the plant fiber is 10-120 KGy; Furthermore, the mechanochemical modification is specifically as follows: mixing the irradiated degraded plant fibers with water, then adding sodium hydroxide solution to adjust the pH to 11-12, using a refiner to perform a pulping treatment, and stopping the pulping when the beating degree is 60-70°SR to obtain micron-sized cellulose fibers; The high-pressure homogenization specifically comprises: mixing the micron-sized cellulose fibers with water to obtain a suspension, and subjecting the suspension to high-pressure homogenization treatment at a flow rate of 2-20 L / h and a homogenization pressure of 200-1500 bar.
[0013] The present invention also provides a method for preparing a low-cost and high-efficiency transfer coating, comprising the following steps: 1) Mixing the modified functional starch and water and gelatinizing them to obtain a starch solution; 2) Mix the remaining components with the starch solution to obtain the transfer coating.
[0014] Furthermore, the transfer coating has a solid content of 30-50% and a viscosity of 300-1000 mPa·s.
[0015] Beneficial effects of the present invention: The coating of the present invention has low viscosity, high solid content, good drying performance and significant cost advantage, and meets the wet strength requirements of low-weight paper running on large-scale high-speed coating machines, and is particularly suitable for the dual pursuit of high quality and cost-effectiveness in industrial applications.
[0016] The introduction of nanocellulose in the present invention is key. Nanocellulose has good film-forming property and biocompatibility, and has nanometer size effect. The surface is rich in hydroxyl groups, and can be closely combined with pulp fiber under the action of hydrogen bonds, thereby improving the compactness and tensile strength of paper, and preventing ink from diffusing outward from the back of the paper sheet and affecting the transfer effect. In addition, nanocellulose also has the functions of dispersant, reinforcing agent and adhesive in the coating, which helps to improve the smoothness and fluidity of the coating, is easy to level and spread on paper, and improves the coating adaptability. At the same time, by introducing modified groups in nanocellulose, the adsorption capacity of the surface coating to ink is increased, and ink can also be prevented from penetrating to the back of the paper.
[0017] The modified functional starch in the present invention is treated with cationization to graft strong positive groups, and the high-density positive charge sites formed on its surface can efficiently capture anionic ink particles, achieve directional enrichment at the coating interface based on the electrostatic adsorption mechanism, and significantly improve the ink fixation efficiency. This characteristic enables the cationic starch to form a dynamic adsorption layer in the printed coating, and through the charge neutralization effect, the ink particles are anchored at the interface within 0.5-2 seconds, thereby improving the heat transfer efficiency.
[0018] The nanocellulose and modified functional starch in the transfer coating of the present invention both contain cationic groups, have the effect of anion scavengers, can effectively adsorb ink, prevent ink from seeping, improve the quality of thermal transfer in the subsequent thermal transfer process, and present a clear and bright pattern. The combination of nanocellulose and modified starch can effectively adjust the viscosity of the coating and improve the transfer efficiency. Further prevent the problem of excessive use of nanocellulose or starch alone causing the coating viscosity to be too low or too high, poor fluidity, and ineffective transfer.
[0019] The combined use of nanocellulose and modified starch in the present invention can also improve the strength and durability of paper, so that the thermal transfer paper can better maintain its shape and performance when subjected to high temperature and pressure, thereby improving the transfer effect; improving the smoothness and glossiness of the paper or coating surface, and improving its ability to adsorb ink. During the thermal transfer process, the ink can be more evenly attached to the paper surface, presenting a clearer and brighter pattern. DETAILED DESCRIPTION
[0020] The present invention provides a low-cost and high-efficiency transfer coating, which is composed of the following components in parts by mass: 5-40 parts of modified functional starch; Nanocellulose hydrogel 2-10 parts; Kaolin 0-40 parts; 10~100 parts of water; The preparation method of the modified functional starch comprises the following steps: The starch and the alkali metal hydroxide are mixed and subjected to an esterification reaction to obtain esterified starch; adding anhydride solution to esterified starch to react and obtain sulfonated precursor starch; The sulfonating agent is added to the sulfonated precursor starch to carry out a sulfonation reaction, and the product is washed, dried and crushed in sequence to obtain the modified functional starch.
[0021] In the present invention, the content of the modified functional starch is preferably 10 to 30 parts by mass, and more preferably 15 to 25 parts by mass.
[0022] In the present invention, the content of the nanocellulose hydrogel is preferably 2 to 8 parts by mass, and more preferably 2 to 5 parts by mass.
[0023] In the present invention, the content of the kaolin is preferably 10 to 30 parts by weight, and more preferably 15 to 25 parts by weight. In the present invention, the kaolin is kaolin commonly used in the papermaking industry on the market.
[0024] In the present invention, the water content is preferably 50 to 90 parts by mass, and more preferably 60 to 80 parts by mass.
[0025] In the present invention, the molar ratio of the starch to the alkali metal hydroxide is 10:1-5, preferably 10:3; the alkali metal hydroxide comprises sodium hydroxide; The temperature of the esterification reaction is 30-80° C., preferably 40-70° C., and more preferably 50-60° C.; the time of the esterification reaction is 20-60 min, preferably 30-50 min, and more preferably 40-45 min.
[0026] In the present invention, the starch comprises one or more of wheat starch, corn starch, potato starch and bean starch, preferably wheat starch and / or corn starch; When the acid anhydride solution is added to the esterified starch for reaction, the reaction temperature is 30-80°C, preferably 40-70°C, and more preferably 50-60°C; the reaction time is 2-7h, preferably 3-6h, and more preferably 4-5h; The molar ratio of acid anhydride to esterified starch in the acid anhydride solution is 1:1-1.5, preferably 1:1.
[0027] In the present invention, the molar ratio of the sulfonating agent to starch is 0.5-1.5:3, preferably 0.8-1.2:3, and more preferably 1.0:3; the temperature of the sulfonation reaction is 30-80°C, preferably 40-70°C, and more preferably 50-60°C; the time of the sulfonation reaction is 2-4h, and preferably 3h.
[0028] In the present invention, the sulfonating agent comprises one or more of oleum, chlorosulfonic acid, sulfur trioxide, aminosulfonic acid and sulfite, preferably sulfite, and more preferably sodium bisulfite.
[0029] In the present invention, the preparation method of the nanocellulose hydrogel comprises the following steps: The plant fibers are sequentially subjected to irradiation degradation, mechanochemical modification, and high-pressure homogenization treatment to obtain nanocellulose hydrogel; The nanocellulose hydrogel has a solid content of 1-5%, a diameter of 3-5 nm, and a length of 500-1000 nm.
[0030] In the present invention, the solid content of the nanocellulose hydrogel is preferably 2-3%; the diameter is preferably 4 nm; the length is preferably 600-900 nm, and more preferably 700-800 nm.
[0031] In the present invention, the plant fiber comprises one or more of natural wood pulp, bamboo pulp or cotton pulp, preferably natural wood pulp.
[0032] The radiation degradation dose of the plant fiber is 10-120 KGy, preferably 20-100 KGy, and more preferably 50-80 KGy.
[0033] In the present invention, the mechanochemical modification is specifically as follows: mixing the irradiated degraded plant fiber with water, then adding sodium hydroxide solution to adjust the pH to 11-12, using a refiner to perform a pulping treatment, and stopping the pulping when the beating degree is 60-70°SR to obtain micron-sized cellulose fibers; The high-pressure homogenization specifically comprises: mixing the micron-sized cellulose fibers with water to obtain a suspension, and subjecting the suspension to high-pressure homogenization treatment at a flow rate of 2-20 L / h and a homogenization pressure of 200-1500 bar.
[0034] In the present invention, the mechanochemical modification is to add water to the irradiated plant fiber at a solid-liquid ratio (w:w) of 5% and stir, then add a 10% NaOH solution to adjust the pH value to 11-12, and then use a pulping machine to perform pulping treatment, and stop pulping when the pulping degree is 60-70°SR, take out the pulp, wash, separate and purify it to produce micron-grade cellulose fiber; The high-pressure homogenization treatment first thoroughly washes the prepared micron-sized cellulose fibers with deionized water to remove residual impurities and chemical reagents. Subsequently, the washed micron-sized cellulose fibers are mixed with water in proportion according to the required solid content (e.g., 2%, or adjusted to other suitable solid contents according to specific applications) to form a uniform suspension. Next, the suspension is treated with a high-pressure homogenization device, and the flow rate during the homogenization process is controlled within the range of 2~20 L / h to ensure the balance between treatment efficiency and quality. At the same time, the homogenization pressure is set to 200~1500bar, and this pressure range is intended to effectively break the cellulose structure, promote the uniform dispersion of nanocellulose, and avoid the destruction of the fiber structure caused by excessive treatment. Through the above-mentioned precisely controlled high-pressure homogenization treatment, the morphology and performance of nanocellulose can be further optimized to meet the high standards of subsequent applications. The solid content of the obtained nanocellulose hydrogel is 2%.
[0035] The present invention also provides a method for preparing a low-cost and high-efficiency transfer coating, comprising the following steps: 1) Mixing the modified functional starch and water and gelatinizing them to obtain a starch solution; 2) Mix the remaining components with the starch solution to obtain the transfer coating.
[0036] In the present invention, gelatinization is to mix the modified functional starch with an equal amount of water, and stir at a temperature of 70-100° C. for 1-10 minutes until the starch is completely gelatinized; preferably, stirring at 80-90° C. for 2-8 minutes.
[0037] In the present invention, the solid content of the transfer coating is 30-50%, preferably 35-45%, and more preferably 40%; the viscosity is 300-1000 mPa·s, preferably 400-900 mPa·s, and more preferably 500-800 mPa·s.
[0038] In the present invention, the transfer coating is applied by a knife on the base paper in a coating manner, and the coating amount is 2-4 g / m 2 , preferably 3g / m 2 .
[0039] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0040] Example 1
[0041] Preparation of modified functional starch: Add sodium hydroxide in a molar ratio of 3:10 to corn starch, stir and knead in a kneader for reaction for 30 minutes, then add tetrahydrofuran and maleic anhydride and heat together (molar ratio: corn starch: maleic anhydride: tetrahydrofuran = 10:4:4), react at 60°C for 4 hours, then add sodium bisulfite and water (molar ratio: corn starch: sodium sulfite: water = 10:1:2) and react for 1 hour. Continue to react for 2 hours, then discharge, dry and crush the material.
[0042] Preparation of Nanocellulose Hydrogel: The natural wood pulp is placed in an electron beam accelerator device for irradiation to degrade it to a suitable viscosity, and the irradiation dose is 100KGy; the irradiated and degraded natural wood pulp is stirred with water according to a 5% solid-liquid ratio (w:w), and then a 10% NaOH solution is added to adjust the pH value to 11, and then the pulping is treated with a refiner. When the beating degree of the pulp is tested to be 65ºSR, the pulping is stopped, the pulp is taken out, washed, separated and purified to prepare micron-sized cellulose fibers; the micron-sized cellulose fibers are mixed with water (weight ratio: micron-sized cellulose fibers: water = 1:20) to obtain a suspension, and the suspension is subjected to high-pressure homogenization treatment at a flow rate of 15L / h and a homogenization pressure of 900bar, and finally a nanocellulose hydrogel with a solid content of 5%, a diameter of 3~5nm, and a length of 500~800nm is obtained.
[0043] Prepare the following raw materials by weight: modified functional starch (same as in Example 1): 30 parts, nanocellulose hydrogel: 2 parts, water: 68 parts. After gelatinizing 30 parts of modified functional starch and 30 parts of water, add nanocellulose hydrogel and remaining water, and stir at high speed, with a stirrer speed of 3000 r / min and a stirring time of ≥5 min until the viscosity of the mixed solution drops below 1000 mPa·s, to obtain a thermal transfer coating with a solid content of 30%±1% and a viscosity controlled at 800~1000 mPa·s.
[0044] Then the coating was carried out at a speed of 1000m / min, and the coating base paper was coated with a knife, and the coating amount was 3g / m 2 .
[0045] The transfer rate and other items of the above embodiment were tested, and the test results are shown in the following table: Table 1 High transfer rate thermal transfer formula
[0046] Table 2 Physical indicators of the coating
[0047] Table 3 Coated paper sample test data
[0048] Conclusion: The high transfer rate thermal transfer coating provided by the present invention has low viscosity, good leveling and good ink transfer rate.
[0049] Example 2 Prepare the following raw materials by weight: modified functional starch (same as in Example 1): 15 parts, nanocellulose hydrogel (same as in Example 1): 2 parts, kaolin: 15 parts, water: 68 parts. After gelatinizing 15 parts of modified functional starch and 50 parts of water, add nanocellulose hydrogel, kaolin and remaining water, and stir at high speed, the stirrer speed is 3000r / min, the stirring time is ≥5min, until the viscosity of the mixed solution drops below 1000mPa·s, and the solid content of the thermal transfer coating is 30%±1%, and the viscosity is controlled at 300~600mPa·s.
[0050] Then the coating was carried out at a speed of 1000m / min, and the coating base paper was coated with a knife, and the coating amount was 4g / m 2 .
[0051] The transfer rate and other items of the above embodiment were tested, and the test results are shown in the following table: Table 4 High transfer rate thermal transfer formula
[0052] Table 5 Physical indicators of the coating
[0053] Table 6 Coated paper sample test data
[0054] Conclusion: The high transfer rate thermal transfer coating provided by the present invention has low viscosity, good leveling, high ink transfer rate and fast ink drying speed.
[0055] Comparative Example 1 Prepare the following raw materials by weight: modified functional starch (same as Example 1): 10 parts, kaolin: 20 parts, water: 70 parts. After gelatinizing 10 parts of modified functional starch and 50 parts of water, add kaolin and the remaining water, and stir at high speed, the stirrer speed is 3000r / min, and the stirring time is ≥5min, until the viscosity of the mixed solution drops below 1000mPa·s, and the solid content of the thermal transfer coating is 30±1%, and the viscosity is controlled at 400~1000mPa·s.
[0056] Then the coating was carried out at a speed of 1000m / min, and the coating base paper was coated with a knife, and the coating amount was 4g / m 2 .
[0057] The transfer rate and other items of the above embodiment were tested, and the test results are shown in the following table: Table 7 High transfer rate thermal transfer formula
[0058] Table 8 Physical indicators of coating of comparative example 1
[0059] Table 9 Coated paper sample test data
[0060] Comparative Example 2 Prepare the following raw materials by weight: 10 parts of nanocellulose hydrogel, 20 parts of kaolin, and 70 parts of water. Add 10 parts of nanocellulose hydrogel to 70 parts of water for ultrasonic dispersion. After uniform dispersion, add 20 parts of kaolin and stir at high speed at a speed of 3000 r / min for ≥5 min until the solution is uniformly mixed. The obtained thermal transfer coating has a solid content of 20±1% and a viscosity of ≤100 mPa·s.
[0061] Then the coating is carried out at a speed of 1000m / min, and the coating base paper is coated with a knife, and the coating amount is 2~3g / m 2 .
[0062] The transfer rate and other items of the above embodiment were tested, and the test results are shown in the following table: Table 10 High transfer rate thermal transfer formula Table 11 Physical indicators of coating of comparative example 2
[0063] Table 12 Coated paper sample test data
[0064] Comparative Example 3 Prepare the following raw materials by weight: 15 parts of conventional corn starch, 2 parts of nanocellulose hydrogel (same as in Example 1), 15 parts of kaolin, and 68 parts of water. After gelatinizing 15 parts of conventional corn starch and 60 parts of water, add nanocellulose hydrogel, kaolin and the remaining water, and stir at high speed at a speed of 3000 r / min for ≥5 min until the solution is evenly mixed to obtain a thermal transfer coating with a solid content of 30±1%.
[0065] Then the coating was carried out at a speed of 1000m / min, and the coating base paper was coated with a knife, and the coating amount was 4g / m 2 .
[0066] The transfer rate and other items of the above embodiment were tested, and the test results are shown in the following table: Table 13 High transfer rate thermal transfer formula
[0067] Table 14 Physical indicators of coatings of comparative example 3
[0068] Table 15 Coated paper sample test data
[0069] Conclusion: It can be seen that the use of nanocellulose hydrogel and modified functional starch alone cannot improve the transfer efficiency of the ink, and the ink drying rate is slow; when nanocellulose hydrogel and modified functional starch are used in combination, the transfer efficiency and viscosity of the obtained coating are low, the ink transfer rate is high, and the ink drying speed is fast.
[0070] It can be seen from the above embodiments that the present invention provides a low-cost and high-efficiency transfer coating and a preparation method thereof. The coating of the present invention has low viscosity, high solid content, good drying performance, and significant cost advantages, and meets the wet strength requirements of low-weight paper running on large-scale high-speed coating machines, and is particularly suitable for the dual pursuit of high quality and cost-effectiveness in industrial applications.
[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A low-cost and high-efficiency transfer coating, characterized in that: It is composed of the following components in parts by weight: 5-40 parts of modified functional starch; Nanocellulose hydrogel 2-10 parts; Kaolin 0-40 parts; 10~100 parts of water; The preparation method of the modified functional starch comprises the following steps: The starch and the alkali metal hydroxide are mixed and subjected to an esterification reaction to obtain esterified starch; adding anhydride solution to esterified starch to react and obtain sulfonated precursor starch; The sulfonating agent is added to the sulfonated precursor starch to carry out a sulfonation reaction, and the product is washed, dried and crushed in sequence to obtain the modified functional starch.
2. The low-cost and high-efficiency transfer coating according to claim 1, characterized in that: The molar ratio of the starch to the alkali metal hydroxide is 10:1-5, and the alkali metal hydroxide comprises sodium hydroxide; The temperature of the esterification reaction is 30-80° C., and the time of the esterification reaction is 20-60 min.
3. The low-cost and high-efficiency transfer coating according to claim 1 or 2, characterized in that: The starch comprises one or more of wheat starch, corn starch, potato starch and bean starch; When the acid anhydride solution is added to the esterified starch for reaction, the reaction temperature is 30-80° C. and the reaction time is 2-7 hours; The molar ratio of the acid anhydride to the esterified starch in the acid anhydride solution is 1:1-1.
5.
4. The low-cost and high-efficiency transfer coating according to claim 1, characterized in that: The molar ratio of the sulfonating agent to starch is 0.5-1.5:3, the temperature of the sulfonation reaction is 30-80° C., and the time of the sulfonation reaction is 2-4 hours; The sulfonating agent comprises one or more of fuming sulfuric acid, chlorosulfonic acid, sulfur trioxide, aminosulfonic acid and sulfite.
5. The low-cost and high-efficiency transfer coating according to claim 1, characterized in that: The preparation method of the nanocellulose hydrogel comprises the following steps: The plant fibers are sequentially subjected to irradiation degradation, mechanochemical modification, and high-pressure homogenization treatment to obtain nanocellulose hydrogel; The nanocellulose hydrogel has a solid content of 1-5%, a diameter of 3-5 nm, and a length of 500-1000 nm.
6. The low-cost and high-efficiency transfer coating according to claim 5, characterized in that: The plant fiber comprises one or more of natural wood pulp, bamboo pulp or cotton pulp; The radiation degradation dose of the plant fiber is 10-120 KGy.
7. The low-cost and high-efficiency transfer coating according to claim 5 or 6, characterized in that: The mechanochemical modification is specifically as follows: mixing the irradiated degraded plant fibers with water, then adding a sodium hydroxide solution to adjust the pH to 11-12, using a refiner to perform a pulping treatment, and stopping the pulping when the beating degree is 60-70°SR to obtain micron-sized cellulose fibers; The high-pressure homogenization specifically comprises: mixing the micron-sized cellulose fibers with water to obtain a suspension, and subjecting the suspension to high-pressure homogenization treatment at a flow rate of 2-20 L / h and a homogenization pressure of 200-1500 bar.
8. The method for preparing a low-cost and high-efficiency transfer coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) Mixing the modified functional starch and water and gelatinizing them to obtain a starch solution; 2) Mix the remaining components with the starch solution to obtain the transfer coating.
9. The method for preparing a low-cost and high-efficiency transfer coating according to claim 8, characterized in that: In the step 2), the mixing is performed under high-speed stirring, the rotation speed of the high-speed stirring is 2000-8000 r / min, the high-speed stirring time is ≥5 min, and the high-speed stirring is performed until the viscosity of the solution drops below 1000 mPa·s.
10. The method for preparing a low-cost and high-efficiency transfer coating according to claim 8 or 9, characterized in that: The transfer coating has a solid content of 30-50% and a viscosity of 300-1000 mPa·s.
Citation Information
Patent Citations
Building glass thermal-insulation antifouling paint and preparation method thereof
CN104744982A
Heat transfer printing paint and application thereof
CN105735041A
Production method of modified starch for heat transfer printing paper
CN108129578A
Thermal dye sublimation transfer paper coating with high ink transfer rate and high ink drying rate and preparation method thereof
CN111058331A
Static-free mask filter membrane and preparation method thereof
CN112191051A